PEMBUATAN PROGRAM APLIKASI PENJUALAN TIKET MUSEUM KERATON SURAKARTA BERBASIS WEB - Ita Nilasari; Ery Dewayani; Bagus Mulyawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
Making the program application Surakarta ticket sales web-based Museum is to help staff workers from the Palace Museum to perform transaction processing ticket sales and report generation by using a computerized system. The methodology used in the making of this application program is using SDLC (System Development Life Cycle), where the method consists of the Planning Phase, Analysis Phase, Design Phase and Implementation Phase. Drafting the application program uses multiple helper applications, such as Microsoft Visio 2007 to draft such as Data Flow Diagrams (DFD), Entity Relation Diagram (ERD), Interpersonal Table, Page Hypertest Preprosessor (PHP) as a programming language and MySQL as database , The result of making this application program can assist the Surakarta Palace Museum to facilitate ticket sales transaction process and in preparing reports sales are becoming more efficient and effective.